EPITHET OXYUMORON HYPERBOLA - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
Adjective, epithet-the term stylistics and poetics; from antiquity known from artistic means. To things and phenomena, understanding and h.k.ga figurative characterization of specific features. In most cases, the adjective is also expressed in the means of rave, noun, number, verb (mas-n. like, the dapper of the dice, the day of the Resurrection, The Hoarse spoke). Adjectivation is not just a means of decorating a sentence, a phrase, but it is associated with content, manifested in logical, psychological, linguistic, literary and other aspects of speech. In contrast to the simple logical definition that distinguishes an object from its other types (such as"murgash poem"), Adjectivation distinguishes either a bironbir feature of the object ("chetan chariot") or, as an istioral epithet, transfers to it a characteristic characteristic of another object (such as"silver winter", "Emerald spring", "Flying Horse"). In folk oral poetic creativity, simple and constant adjectives are used a lot (such as" Pahlavan boy"," maid"," flying carpet"). Some S in the eastern and including Uzbek classical literature.the lar (such as" almond"," pistadahan"," Cypress") has become much repeated and, as a result of its constant occurrence, transformed into compound adjectives — complex adjectives (such as" almond girl"," Cypress juvon"). There will be adjectives characteristic of each stage of literary and historical development. In the system of adjectives, the style of a particular literary era, direction, writer is reflected.